A pessoa com epilepsia: percepções acerca da doença e implicações na qualidade de vida - Hopker, Christiane Del Claro (2015)
Objective: to analyze the perceptions of person with epilepsy about the disease and the impact it might have on their life quality. Method: this is a qualitative and quantitative cross-sectional study conducted in a tertiary referral hospital, linked to the Brazilian National Health System. Thirty (30) people with medically refractory temporal lobe epilepsy selected in Neuroepilepsy clinic participated in the study. To collect the data concerning the perceptions of patients about the disease a questionnaire was administered individually. The responses were recorded in audio and transcribed later in full. After reading the empirical material it was selected fragments and excerpts of the answers according to the criteria of relevance, and grouped by similarity of content in four areas / categories: 1) Perceptions about epilepsy: definitions and causes; 2) Perceptions about epilepsy: seizures and treatment; 3) Perceptions about epilepsy: family and social impact; 4) Perceptions about epilepsy: impact on the lives of PWE. To collect quality of life data and stigma, it was used during the interview methods: Subjective Handicap of Epilepsy and the Stigma Scale of Epilepsy. Results: of the participants, seventeen (17) were female, age ranging from 19 to 58 years (mean 44.8 years). Patients could suffer from the disease affection by 18 to 54 years, with an average of 41.7 years. Monthly crisis often comprehended one to nine attacks, with an average of 4.4 seizures/month. Of those interviewed, 15 had incomplete first degree; ten had complete high school, and five had elementary school. a) In the relationship between stigma and life quality it was found significance in the work domain and the social/personal domain. b) There was also significant difference between stigma and perceptions about epilepsy knowledge. c) When analyzing epilepsy impact on lives and life quality, there was significance with self-perception and the social/ personal domains. Conclusion: the research showed that knowledge and perception of people with epilepsy about the disease greatly influences the way they face the life with epilepsy. The results found of quality of life and stigma confirmed the discrimination, prejudice, beliefs that still exist. As well as the influence of these factors on stigmatizing the PWE to achieve education, job, or at least to keep the job and the relationship with the community. Levels of knowledge of the disease, the misinformation of society, contribute to increased stigma and poor quality of life. It was found problems as the unilateralism in decisions, carried out only by the health professionals, the lack of participation in the decisions concerning the care and treatment of person with epilepsy. We emphasize the need to develop educational activities appropriated to the ability to understand people, to provide greater knowledge of the disease to the patient and their families. In addition to improved quality in patient care, conduct the communication between health professionals and patients providing their participation in the management of their treatment, so their empowerment.